Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Studi Pada Pelanggan PT KAI DAOP 8 Surabaya) - Ryan Fiqih TriHidayat; Lia Nirawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
It is known that today's transportation is very diverse. There are a lot of options that customers can choose according to their preferences and budget. PT KAI DAOP 8 Surabaya was chosen as the research object because it is a large transportation company that has been established for a long time in the Surabaya City area. The purpose of this research is to determine the effect of service quality (X1) and facilities (X2) on customer loyalty (Y) through customer satisfaction (Z). The data collected is in numerical form and analyzed using SPSS, so the method used is quantitative. Data collection was carried out by distributing questionnaires and documentation. The population of this study are people who have used the services of PT KAI DAOP 8 Surabaya. The research sample was 100 respondents. The research results show that service quality and facilities have a significant effect on customer loyalty. The quality of service and facilities significantly influences customer satisfaction. Customer satisfaction significantly influences customer loyalty. The quality of services and facilities affects customer loyalty indirectly and significantly through customer satisfaction.